TINDAKAN POLRI DALAM PENYIDIKAN APABILA TEMPAT KEJADIAN PERKARA BELUM DIKETAHUI SECARA PASTI DALAM PRAKTEK - Rosadi rosadi (Journal of Law ( Jurnal Ilmu Hukum ), 2014)
ABSTRACT The relationship between the crime scene reconstruction is to justify the description of the suspect that was made by investigators for the purposes of criminal investigations to be adapted to the circumstances in the actual scene. In practice, the reconstruction is not done in the actual scene. It is solely for the safety of the suspects alone to avoid the wrath of the public. In addition to that, also for pressing reconstruction costs to a minimum, especially if the scene where the reconstruction will be held just outside of town. But if the scene is not being out of town, the reconstruction is still being done in the actual scene. If the scene its not known with certainty, the efforts undertaken are: Perform the action by way of prosecution which is a technique of investigation it was revealed that a criminal case, where the techniques of this investigation will obtain answers to these questions in terms of investigating a criminal case; To conduct the interrogation of reporting the incident and request information from the patient witnesses, expert witnesses and witnesses who know the first time this criminal case. Despite the difference in area between the crime scene with the region where the discovery of a victim of crime or not deter the police to uncover the criminal case, because despite the differences in the area police can still work together with each other